Reinforcement Enhancing Effects of Nicotine Via Patch and Nasal Spray - Perkins, Kenneth A (Nicotine Tob Res, 2018)
INTRODUCTION: Confirming preclinical findings, nicotine in humans (via smoking) enhances reinforcement from nondrug rewards. Recent demonstration of similar effects with nicotine via e-cigarettes suggests they may also occur when using nicotine replacement therapies (NRT). METHODS: Effects of nicotine via NRT patch or nasal spray were assessed on responding reinforced by music, video, or monetary rewards, or for no reward (control). Nontreatment seeking smokers (N = 31) participated in three virtually identical experimental sessions, each following overnight abstinence (CO ≤ 10 ppm). In a fully within-subjects design using a double-dummy procedure, these sessions involved: (1) nicotine patch (Nicoderm 14 mg) plus placebo spray, (2) placebo patch plus nicotine spray (Nicotrol, 2 × 1 mg/trial), or (3) placebo patch plus placebo spray. Session order was counter-balanced. RESULTS: Relative to placebo, reinforced responding due to nicotine via spray or patch was greater for video reward (both p < .01) but not for music reward (both p > .10). Similar results for NRT spray and patch confirms preclinical findings indicating no difference between fast and slow nicotine delivery, respectively, on reinforcement enhancing effects. Withdrawal relief was unrelated to these effects of nicotine via NRT on nondrug reinforcement. CONCLUSIONS: Nicotine from NRT has some reinforcement enhancing effects in humans, possibly in a manner consistent with nicotine via e-cigarettes but not tobacco smoking. Our findings could suggest differential dose-dependency of available rewards to enhanced reinforcement by nicotine. Such effects may help contribute to the efficacy of NRT for aiding smoking cessation, but more research focusing on dose-dependency of these nicotine actions is needed. IMPLICATIONS: Acute nicotine from smoking enhances reinforced responding for nondrug sensory rewards. Yet, nonsmoked nicotine, including from NRT medications of patch and nasal spray, may act more selectively across rewards, perhaps due to lower dosing exposure. Our results suggest that nicotine via NRT enhances responding for visual (video) reward, but not from auditory (music) reward, just as in prior results using e-cigarettes. Withdrawal relief from NRT was unrelated to reinforced responding, consistent with positive (and not negative) reinforcement from this nicotine. Further research evaluating the dose–response effects of nicotine may clarify differences in enhanced reinforcement depending on the type of available reward.